2022
DOI: 10.1186/s12974-022-02587-8
|View full text |Cite
|
Sign up to set email alerts
|

Captopril alleviates epilepsy and cognitive impairment by attenuation of C3-mediated inflammation and synaptic phagocytosis

Abstract: Evidence from experimental and clinical studies implicates immuno-inflammatory responses as playing an important role in epilepsy-induced brain injury. Captopril, an angiotensin-converting enzyme inhibitor (ACEi), has previously been shown to suppress immuno-inflammatory responses in a variety of neurological diseases. However, the therapeutic potential of captopril on epilepsy remains unclear. In the present study, Sprague Dawley (SD) rats were intraperitoneally subjected to kainic acid (KA) to establish a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 55 publications
(66 reference statements)
1
19
0
Order By: Relevance
“…61 Recent studies have shown that albumin generated by BBB damage can penetrate the intercellular space in the brain, then activate TGF-β signaling pathway changes in astrocytes and destroy the potassium buffering capacity and glutamate metabolism, causing an increase in nerve excitability and lowers the seizure threshold. 62 Studies have suggested that a profound interaction between inflammation and epilepsy, 63 which indicates blocking unwanted inflammatory signals in the brain may provide new strategies for treating epilepsy.…”
Section: Abnormal Ion Channel Functionmentioning
confidence: 99%
“…61 Recent studies have shown that albumin generated by BBB damage can penetrate the intercellular space in the brain, then activate TGF-β signaling pathway changes in astrocytes and destroy the potassium buffering capacity and glutamate metabolism, causing an increase in nerve excitability and lowers the seizure threshold. 62 Studies have suggested that a profound interaction between inflammation and epilepsy, 63 which indicates blocking unwanted inflammatory signals in the brain may provide new strategies for treating epilepsy.…”
Section: Abnormal Ion Channel Functionmentioning
confidence: 99%
“…The study by Dong et al interrogated the role of inflammation and immune complement signaling in the generation of epileptic networks in a mouse model of kainic acid (KA)-induced status epilepticus (SE) and acquired temporal lobe epilepsy. 3 …”
Section: Commentarymentioning
confidence: 99%
“…To address this question, Dong et al utilized captopril as a potential suppressor of C3 signaling, inflammation, and KA-induced epileptogenesis. 3 …”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations